INDONESIAN THEATER 1985-1995: A PERSPECTIVE OF DESCRIPTION PROCESSES SOCIAL CHANGE AND VALUE - Mohamad Zaelani (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThis research seeks to depict the history of Indonesian theater development from 1985 to 1995. This period is deliberately chosen because at that time it is seen that New Order power reached the top of its consolidation. Is there correlation between theater as a part of the reflection of society's expression and the repressive-authoritarian situation of the New Order government? With the approach of sociology of art, during that period, theater in Indonesia reflectedthe changes in society socially and in terms of values. One of these changes was the collapse of the conception of human wholeness (in terms of flesh and blood) in theater in Indonesia, because humans weremerely the object of the state power that tended to be authoritarian.Keywords: Indonesian theater 1985-1995, social changes and values, silent theater, theater ideas.